EFFECTS OF VITAMIN E AND COENZYME Q10 SUPPLEMENTATION AGAINST DOXORUBICIN-INDUCED NEUROTOXICITY IN RATS:ROLE OF APOPTOSIS - Ibrahim, Manal Abdulkhaliq; Al-shawi, Nada Naji (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This work was designed to investigate the effect of Vitamin E and the coenzyme Q10 (CoQ10) supplementation on neurotoxicity induced by doxorubicin (DOX) in rats. Methods: Forty-nine adult Albino rats of both sexes were utilized in this study; animals were randomly enrolled into seven groups of seven animals each. Group I: Control (rats administered corn oil); Group II: Vitamin E at a dose of 100 mg/kg/day for 3 weeks; Group III: CoQ10 at a dose of 50 mg/kg/day for 3 weeks; Group IV: DOX (2.5 mg/kg) intraperitoneally (IP) injected every other day for 2 weeks; Group V: Vitamin E (100 mg/kg/day) orally administered for 3 weeks prior to a DOX 2.5 mg/kg IP injected every other day for 2 weeks; Group VI: CoQ10 (50 mg/kg/day) for 3 weeks orally administered prior to an IP dose of DOX 2.5 mg/kg every other day for 2 weeks; and Group VII: CoQ10 (50 mg/kg/day), Vitamin E (100 mg/kg) for 3 weeks orally administered prior to an IP dose of DOX 2.5 mg/kg every other day for 2 weeks. Twenty-four hour after the end of the treatment duration, brain of each animal was excised and part of it to be utilized to prepare homogenate for the estimation of caspase-3 (CASP-3), and the remaining part is used for immunohistochemistry examination and to estimate the percent of apoptotic index by terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labeling (TUNEL) assay. Results: Vitamin E and CoQ10 significantly (p<0.05) reduced CASP-3, reduced the percent apoptotic index of TUNEL-assay, and there was an improvement in the immunohistochemistry of rats' brain in Groups V, Group VI, and group VII by reducing number of apoptotic cells compared to Group IV. Conclusion: Both Vitamin E and CoQ10 may have a protective effect against DOX-induced neurotoxicity in rats.